Akurasi Diagnostik dan Analisis Gambaran Sitomorfologi Biopsi Aspirasi Jarum Halus pada Lesi Kelenjar Liur Berdasarkan Klasifikasi The Milan System for Reporting Salivary Gland Cytology (MSRSGC) - Lisnawati; Fossetta Manatar, Amelia (Majalah Patologi Indonesia, 2022)
BackgroundFine needle aspiration cytology (FNAC) is an effective, simple, and safe method of assessing salivary glandular lesions. The diagnosis of FNAC can be challenging for pathologists because of the heterogeneous morphological spectrum and overlapping of cytomorphologic salivary glands. The aim is to determine the diagnostic accuracy and analyze the cytomorphology of salivary glands aspiration based on The Milan System for Reporting Salivary Gland Cytology (MSRSGC). Methods A search for cytological preparations for salivary gland lesions in 2015-2019 was carried out in the archives of the Department of Anatomic Pathology, FKUI/RSCM. There were 215 cases of cytology of salivary gland lesions which re-evaluated and classified based on MSRSGC. There were 106 cases of cytologic-histopathologic paired data, 25 of which were excluded because the specimens were not filled the criteria for re-examination. ResultsThere were 81 cases of salivary gland lesions since 2015-2019 which were assessed and reclassified based on MSRSGC, consisting of 8 non-diagnostic, 1 non-neoplastic, 1 case of atypical of undetermined significance (AUS), 39 benign tumors, 10 salivary gland neoplasm of undetermined malignant potential (SUMP), 6 suspicious for malignancy (SFM) and 16 malignant tumors. Three of these cases had a different diagnosis result in false-negative on non-diagnostic and benign tumors. The sensitivity value was 91.17%, specificity 97.43%, positive predictive value (PPV) 96.87%, negative predictive value (NPV) 92.68% and 94.52% accuracy. ConclusionThe diagnosis of fine needle aspiration cytology can be accurately achieved by a combination of clinical information and radiological examination, however a histopathologic examination is still required for definitive diganosis. MSRSGC classification is very helpful in the diagnosis of salivary gland cytology.